2019
DOI: 10.4236/psych.2019.107067
|View full text |Cite
|
Sign up to set email alerts
|

A Need-Supportive Intervention Delivered to English Language Teachers in Colombia: A Pilot Investigation Based on Self-Determination Theory

Abstract: Teachers can be trained to support the basic psychological needs of their students. An important question is whether teachers in economically disadvantaged countries (Colombia, for example) who learn about the principles of need support can facilitate the process of internalization in their students. Using self-determination theory, in the present research we describe several outcomes associated with a pilot study of an intervention that was delivered to English language teachers in and around Medellín, Colomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Ample research has shown that individuals who are in positions of responsibility, such as managers, can be trained on how to support the basic psychological needs of others (Su & Reeve, 2011;cf. ;Niemiec & Muñoz, 2019) (Redeker et al, 2019). Although several high-quality longitudinal studies have revealed a negative relation of job demands (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ample research has shown that individuals who are in positions of responsibility, such as managers, can be trained on how to support the basic psychological needs of others (Su & Reeve, 2011;cf. ;Niemiec & Muñoz, 2019) (Redeker et al, 2019). Although several high-quality longitudinal studies have revealed a negative relation of job demands (e.g.…”
mentioning
confidence: 99%
“…Ample research has shown that individuals who are in positions of responsibility, such as managers, can be trained on how to support the basic psychological needs of others (Su & Reeve, 2011; cf. ; Niemiec & Muñoz, 2019). To our knowledge, though, no research has explored the possibility of training individuals who are in positions of responsibility to reduce factors that are likely to be perceived as need frustrating.…”
mentioning
confidence: 99%